ДЕЯТЕЛЬНОСТНО-ЛИНГВОКУЛЬТУРОЛОГИЧЕСКИЙ АСПЕКТ ПРОЦЕССА ПОНИМАНИЯ ТЕКСТА - Боженкова, Раиса; Боженкова, Наталья (Studia Rossica Posnaniensia, 2008)
In this work modem scientific interpretation of understanding is described from the active-Iinguacultural point of view. This article presents the process of understanding as a creative work and helps the author to form linguacultural sense of the text. The text is constantly enriched by adding cultural sensible aspects of a man who is reexamining the world of subjects connected with his practical and spiritual mastering.